Boundary-layer theory - Schlichting, Hermann; Gersten, Klaus; Krause, Egon; Oertel, Herbert, Jr; Mayes, Katherine (Springer, 2017)
This new edition of the near-legendary textbook by Schlichting and revised by Gersten presents a comprehensive overview of boundary-layer theory and its application to all areas of fluid mechanics, with particular emphasis on the flow past bodies (e.g.